2018
DOI: 10.1021/acs.jmedchem.7b00530
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Guided Synthesis and Mechanistic Studies Reveal Sweetspots on Naphthyl Salicyl Hydrazone Scaffold as Non-Nucleosidic Competitive, Reversible Inhibitors of Human Ribonucleotide Reductase

Abstract: Ribonucleotide reductase (RR), an established cancer target is usually inhibited by antimetabolites which display multiple cross-reactive effects. Recently, we discovered a naphthyl salicyl acyl hydrazone-based inhibitor (NSAH or E-3a) of human RR (hRR) binding at the catalytic site (C-site) and inhibiting hRR reversibly. We herein report the synthesis and biochemical characterization of 25 distinct analogs. We designed each analog through docking to the C-site of hRR based on our 2.7Å X-ray crystal structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…A hRRM1 dimer with lead compound NSAH bound to the C-site (PDB ID: 5TUS) was used as a model for the docking of the new compounds 35 . It was assumed that the primary site of binding for these compounds would be the C-site, because NSAH and all previously studied derivatives of NSAH have demonstrated a preference for the C-site 35 , 37 . Our studies showed that compounds TP2–7 , 9–10 are longer and therefore extend beyond NSAH, allowing for the possibility of more interactions (Figure 3(A–D) and Supplemental Figure 1(B–F)).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A hRRM1 dimer with lead compound NSAH bound to the C-site (PDB ID: 5TUS) was used as a model for the docking of the new compounds 35 . It was assumed that the primary site of binding for these compounds would be the C-site, because NSAH and all previously studied derivatives of NSAH have demonstrated a preference for the C-site 35 , 37 . Our studies showed that compounds TP2–7 , 9–10 are longer and therefore extend beyond NSAH, allowing for the possibility of more interactions (Figure 3(A–D) and Supplemental Figure 1(B–F)).…”
Section: Resultsmentioning
confidence: 99%
“…In silico docking of the compounds was performed using the Glide module of the Schrödinger 2017–3 modelling software suite as previously described 36 , 40–42 . The docking site for the C-site was defined as a 5 Å box centred on the lead compound NSAH ( TP8 ) bound to the hRRM1 (PDB code 5TUS) 37 . Compounds were docked to the C-site using Glide SP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, investigators are seeking inhibitors that target RNR more specifically. Two recent papers (13,14) describe exciting results. Ahmad et al (13) and Huff et al (14) described a naphthyl salicyl acyl hydrazone-based compound that inhibits human RNR through binding at the catalytic site.…”
mentioning
confidence: 99%
“…Ahmad et al (13) and Huff et al (14) described a naphthyl salicyl acyl hydrazone-based compound that inhibits human RNR through binding at the catalytic site. Huff et al (14) synthesized 25 analogs, each selected for its docking to human R1 protein, based on the crystal structure of the protein determined by the same group. The most effective analog inhibited human RNR activity with a half maximal inhibitory concentration of 5.3 mM.…”
mentioning
confidence: 99%